1990
DOI: 10.1007/bf01537410
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine interrupts gastrointestinal fed motility pattern in humans

Abstract: The aim of this study was to investigate the hypothesis that during the postprandial period in humans, dopamine interrupts the gastrointestinal motility pattern through a mechanism that is peptide-mediated. Fourteen normal human subjects were studied by means of intestinal manometry. After recording two consecutive migrating motor complexes a 900-kcal solid-liquid meal was given. In eight subjects 30 min after the meal, placebo or dopamine (5 micrograms/kg/min) was infused for 15 min and then the recording con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 15 publications
1
23
1
Order By: Relevance
“…Dopamine has previously been shown to decrease gastric emptying [20][21][22], although this does not appear to have been investigated in ICU patients. It has been well established that opioids reduce gastric motility [23].…”
Section: Discussionmentioning
confidence: 99%
“…Dopamine has previously been shown to decrease gastric emptying [20][21][22], although this does not appear to have been investigated in ICU patients. It has been well established that opioids reduce gastric motility [23].…”
Section: Discussionmentioning
confidence: 99%
“…In experimental animals the activation of DA-2 neural receptors appears to depress digestive motility via an inhibition of acetylcholine release from cholinergic motor neurons that innervate gastrointestinal smooth muscle [8]. Previous work in healthy human volunteers has indicated that short-term dopamine administration may modify the pattern of gastrointestinal motility [9].…”
Section: Introductionmentioning
confidence: 99%
“…Marzio et al suggested that dopamine did not affect somatostatin levels. 23) However, octreotide, a somatostatin analogue, has a longer half-life than somatostatin and stimulates MMC-like activity in the small intestine. 27,28) The release of somatostatin (AUC 0→240 min ) increased by 45.1% with domperidone (Table 1).…”
Section: Resultsmentioning
confidence: 99%